Stochastic loss of silencing of the imprinted Ndn/NDN allele, in a mouse model and humans with prader-willi syndrome, has functional consequences. - Anne Rieusset; Fabienne Schaller; Unga Unmehopa; Valery Matarazzo; Françoise Watrin; Matthias Linke; Beatrice Georges; Jocelyn Bischof; Femke Dijkstra; Monique Bloemsma; Severine Corby; François J Michel; et al. (PLoS Genetics, 2013)
Genomic imprinting is a process that causes genes to be expressed from one allele only according to parental origin, the other allele being silent. Diseases can arise when the normally active alleles are not expressed. In this context, low level of expression of the normally silent alleles has been considered as genetic noise although such expression has never been further studied. Prader-Willi Syndrome (PWS) is a neurodevelopmental disease involving imprinted genes, including NDN, which are only expressed from the paternally inherited allele, with the maternally inherited allele silent. We present the first in-depth study of the low expression of a normally silent imprinted allele, in pathological context. Using a variety of qualitative and quantitative approaches and comparing wild-type, heterozygous and homozygous mice deleted for Ndn, we show that, in absence of the paternal Ndn allele, the maternal Ndn allele is expressed at an extremely low level with a high degree of non-genetic heterogeneity. The level of this expression is sex-dependent and shows transgenerational epigenetic inheritance. In about 50% of mutant mice, this expression reduces birth lethality and severity of the breathing deficiency, correlated with a reduction in the loss of serotonergic neurons. In wild-type brains, the maternal Ndn allele is never expressed. However, using several mouse models, we reveal a competition between non-imprinted Ndn promoters which results in monoallelic (paternal or maternal) Ndn expression, suggesting that Ndn allelic exclusion occurs in the absence of imprinting regulation. Importantly, specific expression of the maternal NDN allele is also detected in post-mortem brain samples of PWS individuals. Our data reveal an unexpected epigenetic flexibility of PWS imprinted genes that could be exploited to reactivate the functional but dormant maternal alleles in PWS. Overall our results reveal high non-genetic heterogeneity between genetically identical individuals that might underlie the variability of the phenotype.